The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1016/0739-7240(92)90026-t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active immunization against growth hormone releasing factor on concentrations of somatotropin and insulin-like growth factor I in lactating beef cows

Abstract: Two experiments were conducted to determine the effects of immunoneutralization of growth hormone-releasing factor [GRF(1-29)-NH 2 ] on concentrations of somatotropin (ST) and insulin-like growth factor I (IGF-I) in lactating beef cows. In Experiment 1, mUltiparous Hereford cows were immunized against 2 mg GRF(l-29)-(GlY)4-Cys-NH2 conjugated to human serum albumin (GRFi, n=3) or 2 mg human serum albumin (HSAi, n=3) at 52 ± 1 d prior to parturition. Boosters (1 mg) were administered on days 12,40 and 114 postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Immunoneutralization of GRF abolishes episodic release of ST and suppresses serum ST and IGF-I in cyclic gilts [38], lactating sows [39], lactating cows [27], growing steers [2,40], and heifers [3]. Administration of booster immunizations to GRFi cows maintained suppressed serum ST and IGF-I throughout the experiment ( Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Immunoneutralization of GRF abolishes episodic release of ST and suppresses serum ST and IGF-I in cyclic gilts [38], lactating sows [39], lactating cows [27], growing steers [2,40], and heifers [3]. Administration of booster immunizations to GRFi cows maintained suppressed serum ST and IGF-I throughout the experiment ( Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Cyclic nulliparous and primiparous Angus and Charolais (n = 43) [3,26] or multiparous Angus and Hereford (n = 12) females [27], previously immunized against GRF or human serum albumin, were used. The 2-to 3-yr-old Angus and Charolais cows weighed 407 ± 11 and 440 ± 14 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking GRF from reaching hypophyseal somatotrophs, either by hypothalamic deafferentation (30), HST (31-33), or active immunization against GRF (34 -36) blocks episodic GH release both in ruminants and swine. Short-term experiments indicated that active immunization against GRF retarded normal growth in cattle (37).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of GH from somatotrophs is regulated by growth hormone-releasing hormone (GHRH) secreted from neuronal terminals adjacent to capillaries of the hypothalamic-hypophyseal portal system in the infundibulum [3–4]. In cattle, the endocrine relevance of GHRH for anterior pituitary gland secretion of GH is demonstrated by observations that concentrations of GH in circulation are reduced in animals immunized against GHRH [57]. However, release of GH is also influenced by many other factors of peripheral and hypothalamic origin, including somatostatin, IGF-I, leptin, neuropeptide Y (NPY), ghrelin, and opioids [8–10].…”
Section: Introductionmentioning
confidence: 99%